El fideicomiso comunitario de tierras como instrumento útil para la generación de vivienda asequible en Perú: retos, potenciales objeciones y oportunidades - Barboza De Las Casas, Gerson (2023)
The Community Land Trust is a collective stewardship land tenure model from the United States that has proven to be effective in both generating and maintaining affordable housing around the world. In this paper, we demonstrate that this model is needed as an alternative in the current housing policies. Subsequently, we identify the elements of the Community Land Trust, in accordance with American regulations and practice. Then, based on a review of the specialized literature, we gather the experiences of the implementation of this model in the United States, England, and Canada, as well as its recent spread in Latin America with the experiences of Puerto Rico and Brazil. Finally, we identify the challenges, potential objections, and opportunities for its implementation in Peru.